EXPERIENTIAL LEARNING AS THE PRECONDITION OF TEACHER’S PROFESSIONAL COMPETENCE DEVELOPMENT - Dobržinskienė, Rasa; Paurienė, Giedrė; Stepanovienė, Aušra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Society is pausing higher and higher requirements for teachers regarding their professionalism, efficiency of activity, personal qualities and other aspects. If we treated teachers’ professional development as a life-long process, we would find alternative learning forms, which enable continuous, individual and flexible learning. It is important to reveal the role of informal learning in the area of life-long learning process because its significance to teacher’s professional competence has not been fully estimated. Knowledge, skills, and abilities that teachers bring into their professional activity, gained as the outcome of informal learning and development, are not adequately valued. Insufficient attention is paid to professionality and contextuality of teacher’s professional competence development. Therefore, it is crucial to perceive experiential learning which determines development of the competence as a constituent part of informal learning. The aim of the article is to reveal the interaction between experiential learning and teacher’s professional competence development. Methodology of the research encompasses both theoretical, namely scientific literature analysis and summary, and empiric research methods. Qualitative research data were collected using biographical-narrative interviews while data analysis and findings are based on Abductive Reasoning Theory according to Peirce, Grounded Theory according to Strauss and Corbin and Formulating Interpretation according to Bohnsack. Scientific literature analysis has revealed that experiental learning is frequently random, spontaneous and unplanned. Due to its nature it is considered as a part of informal learning. The results of the biographical-narrative interviews with teachers show that professional activity provides pedagogues with rich experience and opportunity to develop regarding the contents of the subject taught as well as methodological and personal perspectives.